In vitro antimicrobial activity of methanolic extracts of different Senna didymobotrya (Fresen.) H. S. Irwin & Barneby plant parts - Jeruto, Pascaline; Arama, Peter; Anyango, Beatrice; Akenga, Teresia; Nyunja, Regina A.; Khasabuli, Daniel; Kamundia, John (Editorial Manager® and ProduXion Manager® from Aries Systems Corporation, 2015)
Background: Herbal medicines are used widely for primary health care in Kenya among rural populations where modern medicines are not affordable. The flowers, roots, stems and leaves of Senna didymobotrya have both antifungal and antibacterial activity. Decoctions or infusion are used to treat skin diseases, diarrhoea, malaria, venereal diseases and stomach problems. Methods: Plants were collected from farmers' fields in western Kenya. Stem bark, root bark, leaves, flowers and immature pods were dried and milled. Methanol was used as extractant. The extracts were reconstituted and incorporated into growth media to obtain 2.5%, 5%, 7.5% and 10%. Bioassays were carried out on Escherichia coli, Staphylococcus aureus, Trichophyton tonsurans and Candida albicans. The growth of cultures on the plates was measured over a period of eight days for bacteria and sixteen days for fungi. The area under disease progress stairs was determined and subjected to statistical analysis. Results: The growth of S. aureus was completely inhibited by root bark at 2.5% and the stem bark at 7.5%. Immature pods, flowers and leaves extracts did not have much significant effect. Growth on E. coli was completely inhibited at 7.5% by stem bark extracts while the root bark inhibited growth at 10%. Bioassays on C. albicans showed that all plant part extracts did not have any significant effect on its growth. Growth of T. tonsurans was completely inhibited by immature pods extract at 10%, the leaves and flowers extracts inhibited the growth at 7.5%. The stem and root bark extracts inhibited growth at 5 %. Conclusions: Stem and root bark extracts of S. didymobotrya showed effective antimicrobial activities against S. aureus, E. coli and T. tonsurans at low dosages. There is need to carry our research on these plant part extracts to identify the active phytochemicals that contribute to their high efficacies as compared to other plant parts. On the conservation front, harvesting of root and stem barks may lead to depletion of the plant. Research should focus on the concentration of the active ingredients in the other plant parts so as to increase their efficacy since they regenerate every season.
Keywords: Medicinal plants; bacteria; fungi; Senna didymobotrya; diarrhoea; ringworm